Brown–Vialetto–Van Laere syndrome: Case Report of Dramatic Response to Riboflavin: Brown-Vialetto-Van Laere Syndrome: Case Report of Dramatic Response to Riboflavin - Heidari, Morteza; Ghahvechi Akbari, Masood; ShahbodaghKhan, Golazin; Garshasbi, Masoud; Badv, Reza Shervin; Yousefimanesh, Hossein (Iranian Journal of Child Neurology, 2025)
Brown-Vialetto-Van Laere syndrome (BVVL) is a rare neurodegenerative disorder caused by riboflavin transporter genes SLC52A2 and SLC52A3 variants. It manifests as a combination of cranial nerve palsies and sensorineural hearing loss. This study presents the case of a 5.5-year-old boy with progressive swallowing difficulties, ptosis, severe hearing loss, and a progressive speech disorder. Remarkably, he showed a significant response to high-dose riboflavin supplementation. Subsequent genetic testing confirmed the diagnosis. Whole exome sequencing identified a homozygous missense variant, [c.239G>A; (p.Gly80Asp)], in the SLC52A3, consistent with BVVL 1. It is essential to remember that BVVL is a set of sensorineural hearing loss and a variety of cranial nerve palsies. Riboflavin should be started as soon as possible because it has a crucial role in neuronal preservation and even reverses the disease